2022
DOI: 10.1155/2022/5359540
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Model for Coronary Artery Disease Diagnosis: A Comparative Study of Several Machine Learning Algorithms

Abstract: Background. In today’s industrialized world, coronary artery disease (CAD) is one of the leading causes of death, and early detection and timely intervention can prevent many of its complications and eliminate or reduce the resulting mortality. Machine learning (ML) methods as one of the cutting-edge technologies can be used as a suitable solution in diagnosing this disease. Methods. In this study, different ML algorithms’ performances were compared for their effectiveness in developing a model for early CAD d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 29 publications
(33 reference statements)
0
41
0
Order By: Relevance
“…In predictive research on coronary artery disease diagnosis, SVM outperformed LR, as reported by scholars such as Garavand et al. [33] . In a comparison of methods for predicting survival rates of acute kidney injury patients without renal replacement therapy, MLP demonstrated better performance than LR, as observed by Pattharanitima et al.…”
Section: Discussionmentioning
confidence: 82%
“…In predictive research on coronary artery disease diagnosis, SVM outperformed LR, as reported by scholars such as Garavand et al. [33] . In a comparison of methods for predicting survival rates of acute kidney injury patients without renal replacement therapy, MLP demonstrated better performance than LR, as observed by Pattharanitima et al.…”
Section: Discussionmentioning
confidence: 82%
“…A wide variety of machine-learning techniques can be used to predict biological outcomes from multiple sources of data (Garavand et al, 2022). In this study, models were developed…”
Section: Machine Learning Methods and Parametersmentioning
confidence: 99%
“…Machine learning (ML) is a powerful data analysis technique 14 that leverages algorithms capable of processing complex functions to construct highly accurate predictive models. ML finds applications across various domains of clinical research, enabling breakthroughs such as the detection of COVID-19 15 , the diagnosis of coronary artery disease 16 , the identification of prostate cancer 17 , and the classification of leukemia subtypes 18 . One noteworthy ML algorithm is Random Forest (RF), which belongs to the ensemble learning category.…”
Section: Introductionmentioning
confidence: 99%